2015
DOI: 10.1021/acs.macromol.5b00040
|View full text |Cite
|
Sign up to set email alerts
|

Self-Activation of Poly(methylenelactide) through Neighboring-Group Effects: A Sophisticated Type of Reactive Polymer

Abstract: The present work reports on a reinvestigation of a radical polymerizable lactide derivative since the polymerization properties were only poorly studied in the first publication in 1969. The optically active methylenelactide was polymerized by free radical polymerization in solution using AIBN as an initiator and resulted in isotactic-biased atactic optically active poly(methylenelactide) according to 1 H NMR and 13 C NMR spectroscopies and specific rotation angle measurements [α] 20 D = −38.5 ± 0.5°. The mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…Excess N-VP anion leads to the formation of 3 which can be separated from 2 via flash chromatography. The structure of products 2 and 3 were clearly verified by use of 1 H NMR, 13 C NMR and DEPT spectra, and GC/MS (supporting information). The use of 3 to prepare crosslinked materials via copolymerization with N-VP yields water-swelling materials.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Excess N-VP anion leads to the formation of 3 which can be separated from 2 via flash chromatography. The structure of products 2 and 3 were clearly verified by use of 1 H NMR, 13 C NMR and DEPT spectra, and GC/MS (supporting information). The use of 3 to prepare crosslinked materials via copolymerization with N-VP yields water-swelling materials.…”
Section: Resultsmentioning
confidence: 80%
“…Since the IR band of N ‐MP at 1660 cm −1 differs from that of polymer 5 , some neighbouring group effects between incorporated monomer units are postulated (Fig. ) . To prove this assumption, copolymer 5b consisting of 4 and a 10‐fold excess of styrene was prepared to prevent such neighbouring dipolar interactions statistically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recently reported spatial dipole–dipole interactions between neighboring lactide units were supported by IR spectroscopy, as the interactions causes two separate carbonyl stretching vibrations. This effect may also play a crucial role in the isotactic propagation steps during MLA polymerization [7]. In contrast, the polymer of non-cyclic MAA shows a preferred syndiotactic ( rr ) conformation caused by steric control of the free substituents as indicated by 13 C NMR spectroscopy (Figure S5, Supporting Information File 1).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent NMR study we demonstrated that, poly(MLA) prepared via free radical polymerization contains mainly isotactic units. Furthermore, we found that the polymer attached lactide rings react like activated esters and thus readily undergo quantitative amidation reactions with aliphatic primary amines under mild conditions [7]. In the underlying study, we focused on spatial effects with respect to interactions between neighboring lactide rings.…”
Section: Introductionmentioning
confidence: 99%